Pro Spring 6 with Kotlin : an in-depth guide to using Kotlin APIs in Spring Framework 6 - Späth, Peter; Cosmina, Iuliana; Harrop, Rob; Schaefer, Chris (Apress, 2023)
Master the fundamentals of Spring Framework 6 while learning from the real-world experiences of Spring experts. Over the course of this book, you'll learn how to leverage Spring 6 in tandem with the Kotlin programming language to build complex enterprise applications from top to bottom. From monoliths to cloud native apps for streaming microservices, youll gain insight into every aspect of the process, including transactions, data access, persistence, and web and presentation tiers. As you progress through the book, the authors demonstrate how to run Kotlin with a single command, deploy new utility methods in String class, use Local-Variable Syntax for Lambda Parameters Nested Based Access Control, read/write strings to and from files, and using Flight Recorder. Also, a whole new generation of dependencies are available, and youll see exactly how to make optimal use of them. A full sample application will show you how to apply Spring 6s new tools and techniques and see how they work together. After reading this comprehensive book, you'll be ready to build your own Spring applications using Kotlin. You will: Explore what's new in Spring Framework 6 and the Kotlin APIs it supports Leverage a new generation of dependencies Build complex enterprise monoliths, cloud-native applications, and microservices Master data access, persistence, and transactions Use with Spring Batch, Integration, and other key Spring modules Integrate Spring 6 with Hibernate and other third party APIs and packages.